2020
DOI: 10.1515/jbcpp-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic abnormalities among late-stage non-dialysis chronic kidney disease patients

Abstract: ObjectivesCardiovascular disease (CVD) complication is common among chronic kidney disease (CKD) patients. Thus, knowledge about CVD and ECG abnormalities in CKD are essential due to progressive nature of the disease and increased risk of sudden cardiac death. This study aims to scrutinize the ECG abnormalities among nondialysis late-stage CKD patients.MethodsA descriptive observational study was conducted at Dr. Soetomo General Hospital, Surabaya, Indonesia. Subjects were hospitalized patients with late-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Clinically, anemia is characterized by reduced volume of human peripheral red blood cells [ 8 ], and is associated with weakened immune function, and in severe cases, it myocardial dysfunction and lack of oxygen in severe cases [ 9 , 10 ]. EPO is an active glycoprotein secreted by the human kidney, which can stimulate the proliferation of red blood cells through binding to EPO receptors on the surface of red blood cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, anemia is characterized by reduced volume of human peripheral red blood cells [ 8 ], and is associated with weakened immune function, and in severe cases, it myocardial dysfunction and lack of oxygen in severe cases [ 9 , 10 ]. EPO is an active glycoprotein secreted by the human kidney, which can stimulate the proliferation of red blood cells through binding to EPO receptors on the surface of red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Also, anemia is associated with low immune function, myocardial damage, and hypoxia. Modern medicine believes that the decreased secretion of erythropoietin (EPO) produced by the kidneys, insufficient raw materials such as iron and folic acid and the inhibition of bone marrow hematopoiesis are contributors to CKD with anemia [ 9 , 10 ]. EPO is an active glycoprotein secreted by the kidney, which stimulates erythrocyte proliferation through binding to EPO receptors on the surface of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, for patients with previously diagnosed CKD, the usefulness of the HF diagnostic algorithm currently proposed may be considered questionable [1] (Figure 2). [1,[10][11][12][13][14][15][16][17]. The HF diagnostic algorithm (left) includes symptoms that are common in patients with CKD, with or without HF (center).…”
Section: How To Confirm or Rule Out Hf In A Patientmentioning
confidence: 99%
“…This may explain a greater tolerance to hyperkalemia and fewer abnormal changes in the ECGG. 34 , 35…”
Section: Discussionmentioning
confidence: 99%
“…This may explain a greater tolerance to hyperkalemia and fewer abnormal changes in the ECGG. 34,35 Mulia et al described the most common ECG abnormalities were the prolonged QTc interval (36.6%), fragmented QRS complex (29.8%), poor R wave progression (24.6%), and peaked T wave (22%). 27 Powell et al demonstrated no difference in ECG changes between acute and chronic hyperkalemic groups.…”
Section: Dovepressmentioning
confidence: 99%